2017
DOI: 10.1111/are.13464
|View full text |Cite
|
Sign up to set email alerts
|

A metabolic approach to understanding adaptation to sea water by endangered Persian sturgeon,Acipenser persicusfingerlings

Abstract: In this study, metabolic responses of Persian sturgeon fingerlings to hyperosmotic condition were investigated by NMR-based metabolomics. Persian sturgeon fingerlings (n = 2010, mean total weight: 3.2 AE 0.6 g; mean total length: 8.5 AE 1.5 cm)were held in freshwater (FW) for 96 hr and then acclimated in brackish water (BW) (12 g/L) for 24 hr. Blood samples were taken before and after salinity acclimation.The major metabolite changes corresponding to salinity acclimation were related to amino acids, osmolytes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…studied the effects of sesamin on the liver and white muscle metabolism in Salmo salar using 1 H-NMR metabolomics, the metabolism level of metabolic products related to energy metabolism such as glucose, glycogen, and leucine changed significantly [ 53 ]. In Acipenser baerii exposed to osmotic stress, it was found that the changes of main metabolic products caused by salt acclimation were related to amino acids, osmotic pressure, and energy metabolism [ 54 ]. Additionally, different levels of protein in the diet will lead to different activities of key enzymes in glycolysis and changes in blood sugar content in the body.…”
Section: Discussionmentioning
confidence: 99%
“…studied the effects of sesamin on the liver and white muscle metabolism in Salmo salar using 1 H-NMR metabolomics, the metabolism level of metabolic products related to energy metabolism such as glucose, glycogen, and leucine changed significantly [ 53 ]. In Acipenser baerii exposed to osmotic stress, it was found that the changes of main metabolic products caused by salt acclimation were related to amino acids, osmotic pressure, and energy metabolism [ 54 ]. Additionally, different levels of protein in the diet will lead to different activities of key enzymes in glycolysis and changes in blood sugar content in the body.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, as the salinity increases, the goblet cells in intestine also increase. Hajirezaee et al (2017) found that Persian sturgeon fingerlings rely more on oxidation of glucose to meet energetic requirements of osmoregulation than oxidation of lipids. TEM showed that serosa was longer and more abundant in the salinity group than that in the freshwater group because serosa could increase the absorption area, thus increasing the absorption of water and nutrients to maintain stable osmotic pressure (Ando et al, 2000).…”
Section: Changes In Tissue Structurementioning
confidence: 99%